Depositional Environment of Middle Jurassic Sargelu Formation Based on Petrographical Study in selected wells at Balad, Ajil, and Baiji Oilfields, Central Iraq - Ali H. Dohan; Faris N. Hassan; Lafta S. Kadhim (Tikrit Journal of Pure Science, 2022)
This work were carried out on 193 thin sections from Middle Jurassic Sargelu Formation. These samples are from three wells (Ajil-8, Balad-1 and Baiji-1). Petrographically, the Sargelu Formation composed of skeletal component (radiolaria, pelecypods, calcispheres, planktonic, benthonic foraminifera and ostracods), in addition non-skeletal such as pellets, groundmass of micrite and recrystallized microspars. Many diagenetic processes affected this formation the main which have been recognized are: compaction, micritization, cementation, neomorphism, dissolution, fractures and veins, silicifaction and dedolomitization in addition authigenic minerals (pyrite). Depending on the petrographic studies the following microfacies have been recognized: Lime Mudstone Microfacies which was divided into three submicrofacies (Pelecypodal Lime Mudstone, Radiolarian Lime Mudstone and Planktonic Foraminiferal Lime Mudstone), Wackestone Microfacies which was divided into four submicrofacies  (Radiolarian Lime Wackestone, Halobia Wackestone, Calcispheres Wackestone and Planktonic Foraminiferal Wackestone) and Packstone Microfacies (Halobia Lime Packstone and Peloidal Lime Packstone). The overall characters of these microfacies indicate that the formation was deposited in two different environments: (1) upper Bathyal environment at the lower part (2) Outer shelf environment at the upper part.